Methodologic and Policy Efforts to Improve a National Long COVID Study - Leonard A. Jason (COVID)
Researching COVID to Enhance Recovery (RECOVER) is a National Institutes of Health initiative to improve our understanding of recovery after SARS-CoV-2 infection and to prevent and treat Long COVID. For almost two years, I worked with a RECOVER Task Force called Commonalities with Other Post Viral Syndromes, whose scope was the overlap of Long COVID symptoms and possible pathways with other post-viral syndromes, including Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) and other dysautonomias. In this article, I review how I was selected to be on this Commonalities task force, and my role as chairperson of a subcommittee that accomplished some specific goals, such as being able to introduce ME/CFS-specific symptoms and ways to assess them in the adult and pediatric RECOVER battery. An effort to have a study funded to collect an independent sample of patients diagnosed with ME/CFS before the pandemic was not successful. This commentary outlines the process of working with this Long COVID task force, including steps such as questionnaire development, protocol design, reviews, and policy initiatives. The outcomes of this task force and subcommittee are reviewed, and lessons learned are presented for those with an interest in working toward policy and structural change.